S3-Leitlinie „Vaginale Geburt am Termin“ aus anästhesiologischer Sicht - Helmer, P.; Skazel, T.; Wenk, M.; Von Kaisenberg, C.; Abou-Dakn, M.; Papsdorf, M.; Abu Hmeidan, F.; Kehl, Sven; Meybohm, P.; Kranke, Peter (Anaesthesist, 2021)
The publication of the new S3 guidelines on “full-term vaginal birth” and the guidelines on cesarean section, also published in 2020, provide further steps towards the promotion of evidence-based medicine in obstetrics, even if the exact configuration of neonatal monitoring during birth, in particular, is still the subject of current discussions. The multiprofessionality in the medical supervision of a birth is also fundamentally well-represented in the compilation of the S3 guidelines by the participating actors and specialist societies. Important from an anesthesiological perspective is the fact that neuraxial procedures still represent the gold standard in obstetric analgesia. With remifentanil PCA an alternative option is available that enables a reliable analgesia to be accomplished, e.g. when there are contraindications to performing neuraxial methods, if this is appropriate under the prevailing circumstances (1:1 support and appropriate monitoring). During an uncomplicated birth the strict fasting rules are relaxed. Overall, the guidelines underline the importance of self-determination and self-control for the expectant mother and give the highest priority to the safety and well-being of mother and child; however, this presupposes that the expectant mother is sufficiently informed about the value of neuraxial analgesia. For this it appears to be of importance to initiate information proposals, which go beyond the usual information sessions for parents that are often organized exclusively by midwives.
CRIS-Team Scopus Importer:2021-09-17
Keywords: CTG; Epidural analgesia; Evidence based medicine; Obstetric anesthesia; Remifentanil PCA